Faktor Penyebab Anak Putus Sekolah Menjadi Pekerja Anak di Desa Segati Kecamatan Langgam Kabupaten Pelalawan - Desi Rahma Putri; Wilson Wilson; Ria Rizkia Alvi (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
This study aims to determine the factors that cause school dropouts to become child laborers in Segati Village, Langgam District, Pelalawan Regency. This study uses a descriptive qualitative approach. There were 5 informants in this study. Collecting data using documentation, observation and interviews. The results of this study indicate that the factors that cause children to drop out of school are more dominant in internal factors, namely factors that come from within themselves, although there are also external factors, namely the encouragement of parents to work.